Diversified and Sustainable Business Strategy of Smallholder Farmers in the Suburbs of Taiwan - Ching-Sung Lee; Yen-Cheng Chen; Pei-Ling Tsui; Ming-Chen Chiang (Agriculture, 2022)
Taiwan’s smallholder farmers are transforming into a diversified business model to respond to the transformation of economic structures and the demand for sightseeing and recreation. On that account, it is urgent and valuable at the research level to develop diversified and sustainable business strategies and models for smallholder farmers. There are two goals in this study. First of all, the study formulated the indicators of diversified and sustainable business strategies for smallholder farmers in Taiwan’s suburbs. Second, the study measured the relevant weights of these indicators from the perspectives of experts. The qualitative and quantitative Analytic Hierarchy Process (AHP) was applied in the study, with Taiwan’s agricultural experts being our main subjects to establish the indicators and models for diversified and sustainable business strategies based on their opinions. According to the research results, there were 6 criteria and 25 sub-criteria for smallholder farmers in terms of diversified and sustainable business strategies, among which, catering services topped other criteria; food health and safety outweighed other sub-criteria of diversified and sustainable business strategies for smallholder farmers. The greatest contribution of the study is the establishment of the indicators and models of diversified and sustainable strategies for smallholder farmers in Taiwan’s suburbs and the discovery that catering service can be an important orientation of diversified and sustainable business strategies for smallholder farmers in Taiwan’s suburbs.